On the keV sterile neutrino search in electron capture - Filianin, Pavel; Blaum, K.; Eliseev, S. A.; Gastaldo, Loredana; Novikov, Yu N.; Shabaev, V. M.; Tupitsyn, I. I.; Vergados, J. (Journal of physics. G, Nuclear and particle physics, 2014)
A joint effort of cryogenic microcalorimetry (CM) and high-precision Penning-trap mass spectrometry (PT-MS) in investigating atomic orbital electron capture (EC) can shed light on the possible existence of heavy sterile neutrinos with masses from 0.5 to 100 keV. Sterile neutrinos are expected to perturb the shape of the atomic de-excitation spectrum measured by CM after a capture of the atomic orbital electrons by a nucleus. This effect should be observable in the ratios of the capture probabilities from different orbits. The sensitivity of the ratio values to the contribution of sterile neutrinos strongly depends on how accurately the mass difference between the parent and the daughter nuclides of EC transitions can be measured by, for example, PT-MS. A comparison of such probability ratios in different isotopes of a certain chemical element allows one to exclude many systematic uncertainties, and thus could make feasible a determination of the contribution of sterile neutrinos on a level below 1%. Several electron capture transitions suitable for such measurements are discussed.
Gesehen am 04.09.2020